New Pedagogical Technologies in Teaching Foreign Languages - Karamatovna, Ravshanova Nasiba (International Journal on Integrated Education, 2023)
This article deals with the problem of finding new techniques and ways to increase motivation for learning foreign languages. One of these forms is new pedagogical technologies, the introduction of which contributes to the effective learning of the language. The article defines the concepts of "Pedagogical technology" and "Smart education", which are capable of providing a high level of education that meets the challenges and opportunities of today's world, will allow young people to adapt in a rapidly changing, unstable environment, and will ensure the transition from book content to active content with the help of a single common repository of educational materials in the presence of an analytical search system; an example of working with the site "die Deutsche Welle" is given.